Gaps in the Pairs (Border Rank, Symmetric Rank) for Symmetric Tensors - Ballico, E. (Sarajevo Journal of Mathematics, 2024)
Fix integers m 2, s5 and d2s+2. Here we describe the possible symmetric tensor ranks 2d+s-7 of all symmetric tensors (or homogeneous degree d polynomials) in m+1 variables with border rank s. 2010 Mathematics Subject Classification. 14N05, 15A69, 15A21